Mesopotamia, Syria and Transjordan in the Archibald Creswell photograph collection of the Biblioteca Berenson - Creswell, K. A. C. 1879-1974.; Anastasio, Stefano, (Archaeopress Archaeology, 2023)
Keppel Archibald Cameron Creswell (1879-1974) developed an early interest in Islamic architecture, considering photography as an essential tool for recording architectural artefacts. This volume presents the photographs that concern Mesopotamia, Syria and Jordan, kept today at the Biblioteca Berenson in Florence.